ANALISIS KESULITAN BELAJAR SISWA DALAM MEMAHAMI KONSEP BANGUN DATAR DI KELAS V SD NEGERI 100612 SORIK TAHUN AJARAN 2021-2022 - Riski Handayani (Jurnal Cermatika, 2022)
In this study, the problem raised is the difficulty of students in learning mathematics, generally resulting from several problems that arise in the learning process, there are still many students who have difficulty understanding the concept of flat shapes even though in previous classes they have studied the material but the data obtained show there are still many students who have learning difficulties below the average. This study aims to find out where students have difficulty learning the Bangun Datar material, what factors influence students' mathematics learning difficulties in the Bangun Datar material and what are the teacher's efforts in overcoming students' mathematics learning difficulties at SD Negeri 100612 Sorik. This research is a qualitative research that uses descriptive methods to collect data by using tests and interviews. which was held at SD Negeri 100612 Sorik, from February 30 to March 25, 2022. The data sources in this study were students and mathematics teachers for grade 5 at SD Negeri 100612 Sorik.